A paisagem na Gleba Vila Amazônia: a impressão na fisionomia de terra firme pelos Sistemas Agroflorestais Espontâneos - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
This research analyzes the imprint in the landscape, from the sociodiversity connection networks placed on the spontaneous agroforestry systems (SAFsE) of properties with family agriculture in (Gleba Vila Amazônia), located in the rural area in the east of Parintins municipality -Amazon. The research responds to the following hypothesis: the impression on the landscape physiognomy is given by sociodiversity when the elements (flora, small breed, crops and others) from spontaneous agroforestry systems on geodiversity environments located by one or more members the (men) of the family or only by the woman. For this, it was used in the chapter I, the theoretical reference with contribution in the categories of analysis: complex thinking; landscape imprint; way of life; time-space; geodiversity; agroforestry systems; sociodiversity. The procedure method was the case study articulated with the technique of cultural paths for the geophysical surveys and the studying of the placed elements that constitutes the landscape in the units of family agriculture. Therefore, in order to achieve the general goal of this study, each of the last three chapters responds to a specific objective. Chapter II: The geodiversity characterization from agroforestry systems in Gleba Vila Amazônia describes the relationship between geodiversity and the time-space from the imprint in the landscape physiognomy, starting from the networks connections of sociodiversity, which organizes SAFsE. Chapter III: Strategies for reproducing the life styles by sociodiversity in the different physiographic areas verify in the study of SAFsE, if there is an imprint on the landscape physiognomy coming from ancient human settlements, and who is the agent of sociodiversity, if they are the women or the men. Chapter IV: The complexity in the solid lands systems of Gleba Vila Amazônia identifies in the dry lands (of dystrophic yellow latosol, black soil, espodossolo) the indicators to the environmental durability imprinted in the spontaneous agroforestry systems, family life styles potentiators of familiar agriculture, and the prognosis on the indicators of the non-existence of this sociodiversity in properties without similar imprint. Based on these analyzes, the study allowed the understanding in the intrinsic interaction of geodiversity components, imbricated in the relation time-space when printing ways of life brought from another place by the connection of the sociodiversity networks, placed by all the members of the units of family agriculture, having as reference to the construction of the dwelling, thus configuring the solid land physiognomy of the spontaneous agroforestry systems of Gleba Vila Amazônia.
Keywords: Paisagem; Sistemas Agroflorestais; Sociodiversidade; Pensamento Complexo; CIÊNCIAS HUMANAS: GEOGRAFIA: GEOGRAFIA REGIONAL